2018
DOI: 10.1007/s10943-018-0685-0
|View full text |Cite
|
Sign up to set email alerts
|

Midwifery Students’ Perceptions of Spirituality and Spiritual Care: An Example from Western Turkey

Abstract: This cross-sectional study aimed to explore Turkish midwifery students' perceptions of spirituality and spiritual care and to investigate the factors affecting them. Data were collected from 271 students of the Midwifery Department of the High School of Health of a state university in the west of Turkey using the Spirituality and Spiritual Care Rating Scale. A significant difference was found between belief in the need for spiritual care and the practice of spiritual care during midwifery training and the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
5
1
2
Order By: Relevance
“…Similarly, Wong et al, (2008) found in their research that younger nurses had low perception levels regarding spirituality and spiritual care. Also, Noble and Jones, (2010) indicated that older nurses with more clinical experience had a greater understanding of spirituality and spiritual care than those who were younger and had less experience (Mermer et al, 2019;Noble & Jones, 2010;Wong et al, 2008). Contrary to our results, however, Atarhim et al, (2019), Gönenç et al, (2016), Herlianita et al, (2018), Kaddourah et al, (2018), Melhem et al, (2016) and Kiaei et al, (2015) found no correlation between the age groups and the SSCRS mean scores.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, Wong et al, (2008) found in their research that younger nurses had low perception levels regarding spirituality and spiritual care. Also, Noble and Jones, (2010) indicated that older nurses with more clinical experience had a greater understanding of spirituality and spiritual care than those who were younger and had less experience (Mermer et al, 2019;Noble & Jones, 2010;Wong et al, 2008). Contrary to our results, however, Atarhim et al, (2019), Gönenç et al, (2016), Herlianita et al, (2018), Kaddourah et al, (2018), Melhem et al, (2016) and Kiaei et al, (2015) found no correlation between the age groups and the SSCRS mean scores.…”
Section: Discussioncontrasting
confidence: 99%
“…The reason why the results of the studies conducted in different populations and cultures differ from each other may be due to the different perceptions of spiritual care and the needs of midwives and nurses. Moreover, in many studies conducted on student-midwives/nurses, it was indicated that students had a high perception of spirituality and spiritual care (Akın & Yılmaz, 2020;Dağhan, 2018;Kalkim et al, 2018;Mermer et al, 2019;Puente et al, 2015;Ross et al, 2018). This difference between professional-midwives/nursing and student-midwives/nursing can be interpreted as implying that students learned about spiritual care as part of their school programs; however, this knowledge was not sufficient in terms of applying it to their clinical practice, because spiritual education is an important factor that supports the development of spiritual caregiving competence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The form was developed by the researchers based on the relevant literature. [18][19][20] It had 24 questions about students' sociodemographic characteristics, such as age, sex, marital status, year of study, income level, family type, and awareness of spiritual care.…”
Section: Personal Description Formmentioning
confidence: 99%
“…The literature includes various studies on nursing and midwifery students' perceptions and opinions about spirituality and spiritual care in Turkey and other countries. [18][19][20]…”
Section: Introductionmentioning
confidence: 99%